The Influence of Stock Liquidity, Capital Structure, and Dividend Policy on Company Value in Manufacturing Companies​​​​​ - Daariin Dewi Nabiilah; Nur Imroatus Sholikah; Adinda Nibros Zahira Fasya; Maria Yovita R Pandin (International Publisher, 2025)
The value of manufacturing companies listed on the Indonesia Stock Exchange was examined in this study in relation to capital structure, dividend policy, and stock liquidity. Price to Book Value (PBV), a quantitative technique based on secondary data from 2024, was employed to calculate the company's worth, and analyzed through multiple linear regression using SPSS 27. This study showed that partially, The company's worth was not considerably impacted by its capital structure; only stock liquidity and dividend policy did. Meanwhile , simultaneous test results showed that all three variables simultaneously influenced company value. The model's capacity to describe different firm values was demonstrated by the coefficient of determination was relatively low, so that the majority of changes in company value were caused by other elements outside the study, such as profitability, company size, and market conditions. This finding suggests that the internal variables studied are not yet the primary drivers in assessing the worth of Indonesian manufacturing firms.